Tin-doped iron oxide negative electrode material, preparation method and application thereof

Through the dumbbell-type loose structure of the tin-doped iron oxide negative electrode material, the problem of poor volume expansion and conductivity of the iron oxide negative electrode material in lithium-ion batteries is solved, and a lithium-ion battery with high cycle stability and rate performance is achieved.

CN115719803BActive Publication Date: 2025-04-15SCNU QINGYUAN INSTITUTE OF SCIENCE & TECHNOLOGY INNOVATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211486478.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-04-15
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material iron oxide has problems such as large volume expansion and poor conductivity, which leads to a sharp decline in battery performance during the cycle.

Method used

The tin-doped iron oxide negative electrode material is prepared by hydrothermal method of metal tin and iron trioxide to form a dumbbell-type loose structure to optimize the electrochemical performance of lithium-ion batteries.

Benefits of technology

By doping tin-doped iron oxide negative electrode material, the cycle stability and rate performance of lithium-ion batteries are significantly improved, the cycle life of the battery is extended, and the specific capacity of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115719803B_ABST
    Figure CN115719803B_ABST
Patent Text Reader

Abstract

The present invention provides a tin-doped iron oxide negative electrode material, a preparation method and an application thereof, comprising metallic tin and ferric oxide, wherein the metallic tin is present in the ferric oxide in the form of atomic substitution, and part of the iron atoms in the ferric oxide is replaced by tin atoms to form a tin-doped ferric oxide negative electrode material. The negative electrode material prepared by using the metallic tin and ferric oxide of the present invention can optimize the electrochemical performance of lithium-ion batteries. The negative electrode material developed in this scheme is based on the high conductivity of tin and the buffering effect of the nanostructure on the electrode volume effect. Tin doping and special nanomorphology have a certain improvement effect on improving the capacity and cycle stability of iron oxide lithium-ion batteries, and can contribute to the research and development of high-capacity, high-stability iron oxide-based lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a tin-doped iron oxide negative electrode material, a preparation method and application thereof. Background Art

[0002] The rapid development of electric vehicles urgently requires the research and development of new negative electrode materials suitable for high-energy lithium-ion power batteries. As a new energy storage device, lithium-ion batteries have become a hot research topic due to their high energy density, good cycle stability, high operating voltage, no memory effect, low self-discharge, and green environmental protection and low pollution. They have been widely used in many fields of production and life.

[0003] As we all know, lithium-ion batteries are composed of positive and negative electrode materials and electrolytes, and the structural characteristics of each part of the material will affect the electrochemical performance of the battery. During the charging and discharging process of the battery, lithium ions need to be repeatedly released and embedded between the positive and negative electrodes. Therefore, it is considered an effective method to improve and enhance the performance of lithium-ion batteries by rationally designing the positive and negative electrode materials of the battery.

[0004] Iron oxide, as a transition metal oxide material, exhibits high theoretical specific capacity characteristics and can be used as a new type of high specific capacity lithium-ion battery negative electrode material. However, transition metal oxide negative electrodes (iron oxide, etc.) also have problems such as large volume expansion and poor conductivity, which will cause the active materials inside the electrode system to separate from the conductive and lithium-conducting networks during the charge and discharge cycle, and the battery materials to become inactive, which will further cause the battery performance to decay sharply and become unable to continue working. The specific problems are as follows: Fe2O3 is reduced to single Fe nanocrystals dispersed in the Li2O matrix during lithium insertion, and the highly active Fe nanocrystals catalyze Li2O to generate Fe2O3 during the lithium removal process. However, usually Li + It is not easy to be completely reduced. At the same time, the negative electrode material will undergo severe volume expansion during this process as lithium ions are inserted and removed, causing the crystal structure to become unstable and collapse. This ultimately causes the battery charge / discharge capacity to decay sharply as the number of cycles increases. In addition, the ionic conductivity of iron oxide is also poor. The above factors lead to a large irreversible capacity loss in Fe2O3 negative electrode lithium-ion batteries, and the cycle stability and rate performance are also unsatisfactory. These shortcomings are important factors that limit the widespread use of Fe2O3 as a negative electrode material for lithium-ion batteries. Summary of the invention

[0005] One of the purposes of the present invention is to provide a tin-doped iron oxide negative electrode material.

[0006] Another object of the present invention is to provide a method for preparing a tin-doped iron oxide negative electrode material.

[0007] Another object of the present invention is to provide a method for preparing an electrode using tin-doped iron oxide negative electrode material.

[0008] To achieve the above purpose and solve the above problems existing in the prior art, the negative electrode material prepared by using the metal tin and ferric oxide of the present invention can optimize the electrochemical performance of lithium-ion batteries. The negative electrode material developed in this scheme is based on the high conductivity of tin and the buffering effect of the nanostructure on the electrode volume effect. Tin doping and special nanomorphology have a certain improvement effect on improving the capacity and cycle stability of iron oxide lithium-ion batteries, which can help develop high-capacity and high-stability iron oxide-based lithium-ion batteries.

[0009] The present invention adopts the following scheme: a tin-doped iron oxide negative electrode material, including metallic tin and ferric oxide, wherein the metallic tin exists in the ferric oxide in the form of atomic replacement, and part of the iron atoms in the ferric oxide are replaced by tin atoms to form a tin-doped ferric oxide negative electrode material.

[0010] As a preferred embodiment, the tin-doped iron oxide negative electrode material is a dumbbell-shaped loose structure self-assembled from nanobelts.

[0011] The tin-doped iron oxide negative electrode material of the present invention has a dumbbell-shaped loose structure. This is because when the ferric oxide is hydrothermally nucleated, the presence of tetravalent tin ions in the system promotes the preferential growth of the ferric oxide along the

[110] ,

[120] and

[210] crystal directions, and the exposure degree of the (001) crystal plane increases, thereby forming a nano-sheet structure with a bare (001) crystal plane. These sheet structures are driven by thermodynamics and self-assemble into a dumbbell-shaped loose structure of orderly stacked nanosheets. The dumbbell-shaped loose structure of the tin-doped iron oxide negative electrode material is conducive to the rapid diffusion of lithium ions on the (001) crystal plane, and the electrode material exhibits excellent rate performance. In addition, the orderly stacking of nanosheets can effectively alleviate the serious problem caused by the volume expansion of ferric oxide during the lithiation process, and the cycle stability of the electrode material is greatly improved. It can be seen that the tin-doped iron oxide negative electrode material of the present invention has the characteristics of high rate and long cycle life when used as the negative electrode of a lithium ion battery.

[0012] As a preferred solution, the dumbbell-shaped loose structure has a length of 6-7 μm and a width of 2-3 μm.

[0013] As a preferred solution, in the tin-doped ferric oxide negative electrode material, the tin doping concentration is 1.5%-2.0% by atomic mole.

[0014] The tin-doped iron oxide negative electrode material of the present invention enables the prepared slurry to have good fluidity when manufacturing an electrode, which is beneficial for uniformly coating the negative electrode material on the surface of the current collector.

[0015] The present invention also provides a method for preparing the above-mentioned tin-doped iron oxide negative electrode material, comprising the following steps:

[0016] Step 1, slowly adding a potassium stannate solution of a certain concentration into a ferric chloride solution of a certain concentration, and continuing to stir after the potassium stannate solution is added to obtain a mixed system;

[0017] Step 2: let the mixed system obtained in step 1 stand for a period of time, transfer a certain amount of the mixed system into a reactor, and perform a hydrothermal reaction at 160-190° C. for 3-10 hours in the reactor, and cool to room temperature after the reaction is completed;

[0018] Step 3, transferring the cooling system obtained in step 2 into a container, and discarding the upper liquid after standing in the container, and retaining the lower sediment layer;

[0019] Step 4: Wash the precipitate layer obtained in step 3 with a solvent and dry it to obtain a tin-doped ferric oxide negative electrode material.

[0020] Preferably, in step 1, Fe 3+ With SnO3 2- The molar concentration ratio is 1:0.02-0.04.

[0021] Preferably, the ferric chloride solution in step 1 is prepared from analytically pure ferric chloride hexahydrate, and the potassium stannate solution is prepared from analytically pure potassium stannate trihydrate.

[0022] The present scheme also provides an application of a tin-doped iron oxide negative electrode material, wherein the negative electrode material, a conductive agent and a binder are prepared in a certain mass ratio, slurried with N-methylpyrrolidone and then coated on a copper foil current collector, and then dried, rolled and sliced ​​to form a working electrode.

[0023] Preferably, the conductive agent is Super-P-Li.

[0024] Preferably, the binder is polyvinylidene fluoride.

[0025] The present invention has the following beneficial effects:

[0026] First, the tin-doped iron oxide negative electrode material of the present invention has a dumbbell-shaped loose structure, in which the exposed (001) crystal plane is conducive to the rapid diffusion of lithium ions, and the ordered loose structure of the stacked nanosheets can alleviate the volume expansion problem of ferric oxide. This scheme prepares the tin-doped iron oxide material by a hydrothermal method, which mainly includes three steps: preparation of a colloidal solution, hydrothermal reaction, and centrifugal drying, to prepare dumbbell-shaped tin-doped iron oxide nanoclusters. The two ends of this dumbbell-shaped tin-doped iron oxide nanocluster are composed of many nanosheets arranged in an orderly manner along the dumbbell shape. Due to the presence of the nanosheet constituent unit, the structural material has a large specific surface area as a negative electrode material for lithium-ion batteries, so that the electrochemical performance of iron oxide-based lithium-ion batteries can be improved.

[0027] Second, the electrode made of the negative electrode material of this scheme exhibits excellent cycle stability and rate performance. The negative electrode material made by controlling the hydrothermal reaction time between 5h-10h has a dumbbell-shaped structure of moderate size, and the loose structure can effectively absorb the stress caused by volume expansion to avoid the active material from falling off. When the battery negative electrode is made of this negative electrode material, the battery performance is more stable, and it has the characteristics of high rate and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope photograph of the tin-doped iron oxide negative electrode material prepared in Example 1;

[0029] Figure 2 for Figure 1 Enlarged front view of the dumbbell-shaped structure;

[0030] Figure 3 for Figure 1 Enlarged picture of the top of the dumbbell-shaped structure;

[0031] Figure 4 for Figure 2 Transmission electron micrograph of the apical edge;

[0032] Figure 5 This is the SEM image of the sample prepared in Comparative Example 2: pure FeCl3 after hydrothermal reaction at 180°C for 5h;

[0033] Figure 6 This is the SEM image of the sample prepared in Example 5: Precursor SnO3 2- The concentration is 0.005 mol / L;

[0034] Figure 7 SEM image of the sample prepared in Example 6: Precursor SnO3 2- The concentration is 0.01 mol / L;

[0035] Figure 8This is the SEM image of the sample prepared in Example 8: Precursor SnO3 2- The concentration is 0.05 mol / L;

[0036] Fig. 9 SEM images of samples prepared in Examples 9-11: evolution of hydrothermal reaction for 0.5h, 1h, and 2h;

[0037] Fig.10 SEM images of samples prepared in Examples 12-14: evolution of hydrothermal reaction at 3h, 5h, and 7h;

[0038] Fig.11 TEM image of the sample prepared in Example 4;

[0039] Fig.12 HR-TEM image of the nanosheet in Example 4;

[0040] Fig.13 SAED spectrum of the sample prepared in Example 4;

[0041] Fig.14 This is the element distribution mapping diagram of the sample prepared in Example 4;

[0042] Fig.15 The percentage diagram of element contents of the samples prepared in Example 4;

[0043] Fig.16 XRD pattern of the sample prepared in Example 4;

[0044] Fig.17 It is the data table of Table 1 in the effect embodiment. DETAILED DESCRIPTION

[0045] In order to make the technical means, creative features, objectives and beneficial effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0046] The present embodiment provides a tin-doped iron oxide negative electrode material, the tin-doped iron oxide negative electrode material comprises metallic tin and ferric oxide, wherein the metallic tin exists in the ferric oxide in the form of atomic substitution, and a very small part of the iron atoms in the ferric oxide is replaced by tin atoms to form tin-doped ferric oxide. The tin-doped iron oxide negative electrode material is a dumbbell-shaped loose structure formed by self-assembly of nanobelts.

[0047] The dumbbell-shaped loose structure has a length of 6-7 μm and a width of 2-3 μm. The doping concentration of tin is 1.5%-2.0% by atomic percentage. The tin-doped iron oxide negative electrode material thus formed provides a fast diffusion path for lithium ions and provides a good filling and accommodating space for ferric oxide.

[0048] The present invention also provides a method for preparing the above-mentioned tin-doped iron oxide negative electrode material, comprising the following steps:

[0049] Step 1: dissolve ferric chloride hexahydrate (FeCl3·6H2O) in 150 ml of deionized water at room temperature to prepare a ferric chloride aqueous solution of a certain concentration, and dissolve potassium stannate trihydrate (K2SnO3·3H2O) in 50 ml of deionized water at room temperature to prepare a potassium stannate aqueous solution of a certain concentration.

[0050] Step 2: At room temperature, the potassium stannate solution of step 1 is slowly added to the ferric chloride solution of step 1 under magnetic stirring. After the potassium stannate solution is added, stirring is continued for more than 30 minutes until the colloidal solution is transparent and free of flocs, ensuring the formation of a stable and uniformly dispersed colloidal solution, thereby obtaining a mixed system.

[0051] Step 3: let the mixed system of step 2 stand for more than 24 hours, take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined autoclave, and place the autoclave in an oven at 160-190°C for hydrothermal reaction for 3-10 hours, and cool naturally to room temperature after the reaction is completed.

[0052] Step 4: transfer the cooling system of step 3 into a 200 ml beaker, let it stand for 3 hours, discard the upper liquid, and keep the purple-red precipitate at the lower layer.

[0053] Step 5, washing the purple-red precipitate obtained in step 4 with water three times, and drying it in an oven to obtain a purple-red product.

[0054] Preferably, in step 1, Fe 3+ With SnO3 2- The molar concentration ratio of Fe is 1:0.02-0.04. 3+ The concentration is 0.5 mol / L, SnO3 2- The concentration of the precursor product is 0.01mol / L-0.02mol / L.

[0055] Preferably, the magnetic stirring speed in step 2 is 400 r / min.

[0056] Preferably, the hydrothermal reaction time in step 3 is 3-10 h.

[0057] Example 1

[0058] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.72g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Slowly drip the 50ml potassium stannate solution obtained above into the 150ml ferric chloride solution obtained above under magnetic stirring at room temperature. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for 30min (speed 400r / min) to obtain a mixed system. After the mixed system is allowed to stand for 24h, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.012mol / L. Take 150ml of it and transfer it to a 200ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 180℃ for hydrothermal reaction for 10h. After the reaction is completed, cool it naturally to room temperature. Transfer the cooling system to a 200ml beaker, let it stand for 3h, discard the upper liquid, and retain the purple-red precipitate in the lower layer. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven and dry it to obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0059] Figure 1 This is a scanning electron microscope photo of the tin-doped iron oxide negative electrode material prepared in this example. Figure 2 and Figure 3 They are Figure 1 A zoomed-in photo of the front and top of the medium dumbbell type. Figure 4 for Figure 2 Transmission electron micrograph of the top edge. Figure 1 It can be seen that the tin-doped iron oxide negative electrode material prepared in this embodiment has a uniform dumbbell-shaped structure. Figure 2 and Figure 3 It can be seen that the dumbbell shape is a loose structure formed by stacking thinner strips, with a dumbbell of 6-7μm and a width of 2-3μm. Figure 4 It can be seen that the thin strips are flake structures, and the width of the flakes is 19nm-21nm.

[0060] Example 2

[0061] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.72g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Slowly drip the 50ml potassium stannate solution obtained above into the 150ml ferric chloride solution obtained above under magnetic stirring at room temperature. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for 30min (speed 400r / min) to obtain a mixed system. After the obtained mixed system is allowed to stand for 24h, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.012 mol / L. Take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 180°C for hydrothermal reaction for 5 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system into a 200 ml beaker, let it stand for 3 hours, discard the upper liquid, and retain the lower purple-red precipitate. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven to dry, and obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0062] Example 3

[0063] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.72g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Under magnetic stirring at room temperature, slowly drip the 50ml potassium stannate solution of step one into the 150ml ferric chloride solution of step one. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for more than 30 minutes (speed 400r / min) to obtain a mixed system. After the above mixed system is allowed to stand for 24 hours, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.012 mol / L. Take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 180°C for hydrothermal reaction for 20 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system to a 200 ml beaker, let it stand for 3 hours, discard the upper liquid, and retain the lower purple-red precipitate. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven to dry, and obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0064] Example 4

[0065] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.6g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Under magnetic stirring at room temperature, slowly drip the 50ml potassium stannate solution of step one into the 150ml ferric chloride solution of step one. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for more than 30 minutes (speed 400r / min) to obtain a mixed system. After the above mixed system is allowed to stand for 48 hours, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.01 mol / L. Take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 180°C for a hydrothermal reaction for 4 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system to a 200 ml beaker, let it stand for 3 hours, discard the upper liquid, and retain the lower purple-red precipitate. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven and dry it to obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0066] Embodiment 5-8

[0067] The amounts of potassium stannate trihydrate (K2SnO3·3H2O) in Example 4 were 0.3 g, 0.6 g, 0.72 g, 1.2 g, and 3 g, respectively. The other conditions were the same as in Example 4. After the obtained mixed system was allowed to stand, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentrations of the precursor products are 0.005 mol / L, 0.01 mol / L, 0.012 mol / L, and 0.05 mol / L respectively.

[0068] Take 150ml and transfer it to a 200ml polytetrafluoroethylene-lined autoclave, and place the autoclave in an oven at 180°C for a hydrothermal reaction for 4 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system to a 200ml beaker, let it stand for 3 hours, discard the upper liquid, and retain the purple-red precipitate at the lower layer. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven and dry it to obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0069] Examples 9-14

[0070] The hydrothermal reaction time in Example 4 was 0.5h, 1h, 2h, 3h, 5h, and 7h respectively. The other conditions were the same as in Example 4. After the hydrothermal reactor was naturally cooled to room temperature, the turbid solution or precipitate was centrifuged and washed with deionized water for multiple times. Finally, the obtained precipitate was transferred to a blast drying oven and dried for 12h. The obtained powder was the target product. Fig. 9 and Fig.10 From the comparison of the figures, it can be seen that with the increase of reaction time, the synthesized material gradually changes from disorder to order and uniform dispersion. From the embodiment figure of the reaction for 2 hours, it can be seen that the material presents a clear monodisperse columnar morphology. In the embodiment figure after the reaction for 3 hours, the dumbbell-shaped feature of "big at both ends and small in the middle" can be clearly seen. At the same time, some flocs are also noticed in the figure. It can be seen from the reaction for 5 hours and 7 hours that the dumbbell-shaped structure becomes more and more obvious, and the material size becomes larger and larger, and the randomly distributed flocs no longer exist.

[0071] Embodiment 15

[0072] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.6g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Under magnetic stirring at room temperature, slowly drip the 50ml potassium stannate solution of step one into the 150ml ferric chloride solution of step one. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for more than 30 minutes (speed 400r / min) to obtain a mixed system. After the above mixed system is allowed to stand for 36 hours, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.01 mol / L. Take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 160°C for hydrothermal reaction for 8 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system to a 200 ml beaker, let it stand for 5 hours, discard the upper liquid, and retain the lower purple-red precipitate. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven and dry it to obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0073] Example 16

[0074] Dissolve 27.30g of ferric chloride hexahydrate (FeCl3·6H2O) in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution; dissolve 0.6g of potassium stannate trihydrate (K2SnO3·3H2O) in 50ml of deionized water under magnetic stirring at room temperature to form a colorless solution. Under magnetic stirring at room temperature, slowly drip the 50ml potassium stannate solution of step one into the 150ml ferric chloride solution of step one. This process will produce a large amount of brown precipitate. After adding the potassium stannate solution, continue stirring for more than 30 minutes (speed 400r / min) to obtain a mixed system. After the above mixed system is allowed to stand for 24 hours, Fe 3+ The concentration is 0.5mol / L, SnO3 2- The concentration of the precursor product is 0.01 mol / L. Take 150 ml and transfer it to a 200 ml polytetrafluoroethylene-lined high-pressure reactor, and place the reactor in an oven at 190°C for hydrothermal reaction for 5 hours. After the reaction is completed, cool it naturally to room temperature. Transfer the resulting cooling system to a 200 ml beaker, let it stand for 3 hours, discard the upper liquid, and retain the lower purple-red precipitate. Wash the obtained purple-red precipitate three times with deionized water, put it in an oven and dry it to obtain a purple-red product, which is the tin-doped iron oxide negative electrode material.

[0075] Comparative Example 1

[0076] Dissolve 27.30g of ferric chloride in 150ml of deionized water under magnetic stirring at room temperature to form a brown-yellow solution. Transfer 150ml of the obtained brown-yellow solution to a 200ml polytetrafluoroethylene-lined autoclave, and place the autoclave in an oven at 180°C for hydrothermal reaction for 10h. After the reaction is completed, cool naturally to room temperature. Transfer the obtained cooling system to a 200ml beaker, let it stand for 3h, discard the upper layer of liquid, and retain the lower brick-red precipitate. Wash the obtained purple-red precipitate with deionized water three times, put it in an oven to dry, and obtain a large amount of brick-red product.

[0077] Comparative Example 2

[0078] The amount of potassium stannate trihydrate in Example 4 is 0, and the other conditions are the same as Example 4. Take 150 ml of the obtained brown-yellow solution and transfer it to a 200 ml polytetrafluoroethylene-lined autoclave, and place the autoclave in an oven at 180°C for hydrothermal reaction for 4 hours. After the reaction is completed, it is naturally cooled to room temperature. The obtained cooling system is transferred to a 200 ml beaker, and the upper layer of liquid is discarded after standing for 3 hours, and the lower brick-red precipitate is retained. The obtained purple-red precipitate is washed three times with deionized water, and a large amount of brick-red product is obtained after being placed in an oven for drying.

[0079] Combining Examples 4-8 and Comparative Example 2, it can be seen that, as shown in the figure, keeping all experimental parameters unchanged, in the absence of SnO3 2-In this case, we can obtain Fe2O3 nanoparticles, but from Figure 5 It can be seen that the obtained samples are uneven in size and not perfectly spherical in shape, which may be due to a certain degree of agglomeration during the synthesis process. 2- When the concentration is 0.005 mol / L, spherical particles can be seen in the SEM image, and there are also a small number of dumbbell-shaped particles, which indicates that SnO3 2- The addition of SnO3 has a certain effect on the morphology of Fe2O3, but the concentration of tin is not suitable; when we add SnO3 2- When the concentration is 0.01 mol / L, the synthesized material presents a clear dumbbell shape, and nanorod / nanosheet structures can be seen on the surface of the material. Porous morphology can be seen at both ends of the dumbbell-shaped structure. 2- When the concentration was further increased to 0.05 mol / L, the dumbbell-shaped material composed of nanostructures could no longer be clearly seen in the SEM image. Because the material was not completely reacted, many flocculent substances were seen attached to the surface of the nanorods.

[0080] Taking Example 4 as an example, when the tin doping concentration was 0.01 mol / L, a rough dumbbell-shaped tin-doped iron oxide nanocluster was synthesized, and then EDS, SAED, transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray diffraction energy spectrum (XPS) characterization methods were used to detect the microstructure, elemental composition and distribution of the dumbbell-shaped nanocluster, and DES was used to detect the element distribution.

[0081] In order to further confirm the morphology of dumbbell-shaped Sn-doped Fe2O3 nanoclusters, transmission electron microscopy was used. Fig.11 The image more clearly shows the dumbbell-shaped structure of "small in the middle and large at both ends". Fig.11 It is obvious from the schematic diagram that its surface is not smooth and has uneven "protrusions". In order to gain a deeper understanding of the specific structural morphology of these "protrusions", a high-magnification transmission electron microscope was used to analyze a single "protrusion". The results are as follows Fig.12 As shown, it is proved that these "protrusions" are nanosheets with a width of about 21.2nm. The enlarged HRTEM image clearly shows that the lattice spacing is 0.25nm and 0.43nm, which is consistent with the (110) and (012) planes of standard Fe203, and the (001) crystal plane is exposed on the surface. Combined with the scanning electron microscope image, it can be seen that the two ends of this dumbbell-shaped tin-doped iron oxide nanocluster are composed of many nanosheets arranged in an orderly manner along the dumbbell shape. In this way, due to the existence of nanosheet constituent units, it is further proved that the structural material has a large specific surface area as a negative electrode material for lithium-ion batteries, so that it is expected to improve the electrochemical performance of iron oxide-based lithium-ion batteries.

[0082] Selected electron diffraction was performed on a section of the nanosheet. Fig.13 In the SAED pattern, clear and neatly arranged diffraction lattices can be found, indicating that at 0.01 mol / L SnO3 2- The material synthesized at the concentration is a single crystal. The study proved the element distribution on the surface of the material by EDS characterization test. Fig.14 The EDS mapping diagram shows that the three elements Fe, Sn, and O are evenly distributed in the material, which also explains the elemental composition of the material. Fig.15 The percentages of three elements can be observed in the sample, namely O-75.1%, Fe-23.4%, and Sn-1.60%. Fig.16 It is 0.01mol / L SnO3 2- The XRD images of the Sn-doped iron oxide nanoclusters synthesized at the concentration of 1.5 wt. % show that the diffraction peak position of the sample is consistent with the Sn in the standard PDF card 088-0432. 0.092 Fe 1.874 The diffraction peaks of O3 match well, and no other peaks are observed. The XRD images show that in the synthesized tin-doped iron oxide material, the Sn element replaces part of the Fe element, which further proves that SnO3 in the Fe2O3 nanoclusters 2- Successful doping.

[0083] In this scheme, through the above comparison experiment, the hydrothermal reaction was carried out at 180℃ for 4h to synthesize the tin-doped iron oxide powder material. 2- The material prepared at a concentration of 0.01 mol / L showed evenly dispersed dumbbell-shaped tin-doped iron oxide nanoclusters of comparable size, where a single dumbbell-shaped cluster was 6.58 um long and 2.37 um wide, with its two ends composed of a multi-gap structure consisting of many 21.1 nm wide nanosheets, which also provided a material basis for it to be used as a negative electrode material for lithium-ion batteries with better stability and higher capacity.

[0084] Effect Example

[0085] The negative electrode materials obtained in the above-mentioned Examples 1-3 and Comparative Example 1 were used to make battery electrodes, and their performances were tested according to the following methods.

[0086] Step 1: Battery production: negative electrode material, Super-P-Li and polyvinylidene fluoride are prepared in a mass ratio of 8:1:1, and slurried with N-methylpyrrolidone and coated on the copper foil current collector. After drying, rolling and slicing, the working electrode is formed. The counter electrode and reference electrode are lithium sheets, and the microporous polypropylene membrane is the diaphragm. The electrolyte is a mixed system of ethylene carbonate and dimethyl carbonate with a mass ratio of 1:1 containing 1.0 mol / L LiPF6. The battery is assembled in a high-purity argon-filled glove box.

[0087] The specific process of battery negative electrode material preparation and battery assembly is as follows: the negative electrode material, Super-P-Li and polyvinylidene fluoride are mixed in a ball mill in a mass ratio of 8:1:1, and three times the total mass of NMP of the above materials is added to the ball mill using a pipette. Put 20 large balls and 30 small balls in the ball mill, and circulate 30 times at 50% speed in the ball mill, with 3 minutes in each forward and reverse directions as one cycle; to prevent the slurry from drying out, coating should be carried out immediately after the ball milling is completed; scrape the slurry at the bottom of the ball mill with a medicine spoon and apply it on the clean rough surface of the copper foil. Use the 50mm side of the coater to quickly and evenly coat; after coating, transfer the copper foil to a glass plate, transfer it to a blast drying oven and dry it at 60℃ for 10h. After blast drying, transfer it to a vacuum drying oven and dry it at 100℃ for 10h. The drying time should not be too long, otherwise it will cause the powder to fall off; then press and slice it, and weigh each electrode plate; then place the electrode plate in a vacuum drying oven and dry it at 100℃ for 1h, and then transfer it to an argon glove box; assemble the half-cell in the glove box, from bottom to top, the negative electrode shell, spring, gasket, lithium sheet, diaphragm, homemade electrode plate, and positive electrode shell. It should be noted that 100ul of electrolyte should be added with a pipette before and after placing the diaphragm. Plastic tweezers should be used to prevent the positive electrode shell from being opened and the button battery should not be held directly by hand. Then, the button battery hydraulic sealer is used to press the button battery together; the assembled button battery is left to stand for 12 hours, and its open circuit voltage is measured and recorded for subsequent electrochemical testing.

[0088] Step 2: Test the battery performance at 25±3℃. The steps are as follows:

[0089] Step 21, cycle stability test steps: (1) 1C discharge to 0.005V; (2) 1C charge to 3.0V; cycle 500 times according to the above steps.

[0090] Step 22, rate performance test steps: ① discharge to 0.005V at a current density of 1C; ② charge to 3.0V at a current density of 1C; ③ repeat the above steps for 10 cycles. Change the current density to 2C, 3C, 5C, 3C, 2C in sequence, and repeat the above steps ①-③.

[0091] The battery test structures of the negative electrode materials of various embodiments and comparative examples are shown in Table 1.

[0092]

[0093] As shown in Table 1, the products of Example 1 and Example 2 of the present invention exhibit excellent cycle stability and rate performance. The discharge specific capacity of Example 3 and Comparative Example 1 after 500 cycles at 1C current density is less than 200 mAh / g, and the performance is poor. The rate performance of Example 3 and Comparative Example 1 is also worse than that of Example 1 and Example 2.

[0094] Compared with the product of Example 3, the hydrothermal reaction time of the products of Example 1 and Example 2 is 5h, 10h and 20h respectively. When the hydrothermal reaction time is too long, the dumbbell-shaped structure size increases rapidly after exceeding 10h, which is manifested as excessively large electrode material particles, significant volume expansion, and poor battery performance. When the reaction time is controlled between 5h-10h, the dumbbell-shaped size is moderate, the loose structure can effectively absorb the stress caused by volume expansion, can avoid the active material from falling off, and the battery performance is stable. At the same time, a large number of exposed (001) crystal faces can quickly diffuse lithium ions, which is conducive to improving rate performance.

[0095] Compared with the product of Comparative Example 1, the products of Examples 1 and 2 do not contain potassium stannate trihydrate added to the reaction system of Comparative Example 1, so that the final product is a dumbbell-shaped product with a dense structure, and the sample has no exposed (001) crystal plane. This dense structure is not conducive to the stress absorption caused by volume expansion. At the same time, lithium ions diffuse slowly inside the dense structure, and the battery performance is poor after comprehensive influence.

[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a tin-doped iron oxide negative electrode material, characterized in that: The tin-doped iron oxide negative electrode material comprises metallic tin and ferric oxide, wherein the metallic tin exists in the ferric oxide in the form of atomic replacement, and part of the iron atoms in the ferric oxide is replaced by tin atoms to form a tin-doped ferric oxide negative electrode material, and the tin-doped ferric oxide negative electrode material is a dumbbell-shaped loose structure formed by self-assembly of nanobelts; The specific preparation steps are as follows: Step 1: slowly add a certain concentration of potassium stannate solution to a certain concentration of ferric chloride solution, and continue stirring after the potassium stannate solution is added to obtain a mixed system. The Fe 3+ With SnO3 2- The molar concentration ratio is 1:0.02-0.04, where SnO3 2- The concentration is 0.01 mol / L-0.02 mol / L; Step 2: After the mixed system obtained in step 1 is allowed to stand for a period of time, a certain amount of the mixed system is transferred into a reactor, and the reactor containing the mixed system is subjected to a hydrothermal reaction at 160-190° C. for 3-10 hours, and then cooled to room temperature after the reaction is completed; Step 3, transferring the cooling system obtained in step 2 into a container, and discarding the upper liquid after standing in the container, and retaining the lower sediment layer; Step 4: Wash the precipitate layer obtained in step 3 with a solvent and dry it to obtain a tin-doped ferric oxide negative electrode material.

2. A tin-doped iron oxide negative electrode material, characterized in that: It is prepared by the method for preparing a tin-doped iron oxide negative electrode material as described in claim 1.

3. The tin-doped iron oxide negative electrode material according to claim 2, characterized in that: Each of the dumbbell-shaped loose structures has a length of 6-7 μm and a width of 2-3 μm.

4. The tin-doped iron oxide negative electrode material according to claim 2, characterized in that: In the tin-doped ferric oxide negative electrode material, the doping concentration of tin is 1.5%-2.0% by atomic mole.

5. The use of a tin-doped iron oxide negative electrode material according to any one of claims 2 to 4, characterized in that: The negative electrode material, the conductive agent and the binder are prepared in a certain mass ratio, slurried with N-methylpyrrolidone and then coated on a copper foil current collector, and then dried, rolled and sliced ​​to make a working electrode.

6. The use of a tin-doped iron oxide negative electrode material according to claim 5, characterized in that: The conductive agent is Super-P-Li.

7. The use of a tin-doped iron oxide negative electrode material according to claim 5, characterized in that: The binder is polyvinylidene fluoride.